Segregated versus integrated biodiversity conservation: Value-based ecosystem service assessment under varying forest management strategies in a Swiss case study. (December 2018) - Blattert, Clemens; Lemm, Renato; Thees, Oliver; Hansen, Jan; Lexer, Manfred J.; Hanewinkel, Marc
Graphical abstract: Highlights: Management strategies are evaluated for biodiversity and ecosystem services (BES). BES are assessed with a value-based multi-criteria approach at the enterprise level. It is demonstrated how sectorial models can contribute to local BES research. In a case study, zonewise segregation with multiple strategies is considered best. Zoning offers a compromise combining structural biodiversity aspects and management. Abstract: There is an ongoing debate regarding segregated and integrated approaches to biodiversity conservation in Central European forests. The ecosystem services provisioning of timber, recreation and carbon sequestration are, however, also of great importance. The existence of manifold objectives makes it difficult to find an appropriate strategy in forest management, especially for practitioners at the management unit level. We simulated forest development over 50 years under five management strategies in a Swiss forest enterprise: business as usual (BAU), segregated (BC-seg) and integrated (BC-int) biodiversity conservation, intensive management (INTENS) and no management (NO). INTENS and BAU were used as benchmark strategies. The available forest inventory data was used as input for the growth simulator WaldPlaner. Management strategies were analysed over time with a value-based multi-criteria approach based on 21 indicators regarding the provisioning of biodiversity and ecosystem services (BES) as well as their synergies and conflicts. The analysis yielded the best overall BES values for the strategies INTENS, BAU and BC-seg. However, INTENS and BAU were not envisaged as alternatives for biodiversity conservation because they lack essential late successional forest elements. Strategy NO had the lowest BES values, despite the good biodiversity results of the climax states (micro-habitat bearing large deadwood and large old living trees). Of the two intended conservation strategies integration and segregation, the latter had higher values. Segregation therefore offers a compromise by combining the positive aspects of both conservation and management-oriented strategies. With regard to the case study area, we thus conclude that a small-scale segregation of the forest into zones with multiple management strategies is best for achieving structural biodiversity aspects in multiple-objective forest management.